Aktywność fizyczna i niektóre jej uwarunkowania wśród młodzieży licealnej = Physical activity and some of its conditions amongst secondary-school youth - Kozłowska, Ewelina; Kowalczyk, Anna; Marzec, Agnieszka (Journal of Education, Health and Sport, 2015)
Kozłowska Ewelina, Kowalczyk Anna, Marzec Agnieszka. Aktywność fizyczna i niektóre jej uwarunkowania wśród młodzieży licealnej = Physical activity and some of its conditions amongst secondary-school youth. Journal of Education, Health and Sport. 2015;5(9):386-396. ISSN 2391-8306. DOI10.5281/zenodo.30957 http://dx.doi.org/10.5281/zenodo.30957 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A386-396 https://pbn.nauka.gov.pl/works/624653 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 13.09.2015. Aktywność fizyczna i niektóre jej uwarunkowania wśród młodzieży licealnej Physical activity and some of its conditions amongst secondary-school youth Ewelina Kozłowska1, Anna Kowalczyk2, Agnieszka Marzec3 1Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie 2 Studentka Wydziału Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3Zakład Dietetyki Klinicznej, Uniwersytet Medyczny w Lubinie Adres do korespondencji / Address for correspondence mgr Ewelina Kozłowska Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie ul. Chodźki 1, 20-093 Lublin e-mail: ewelina.kozlowska@umlub.pl Streszczenie Wprowadzenie i cel pracy. Aktywność fizyczna stanowi jeden z kluczowych warunków zdrowego stylu życia. Niestety, jak wynika z analiz zaledwie 30% dzieci i młodzieży podejmuje czynności ruchowe, których rodzaj, częstotliwość i intensywność zaspokajają potrzeby fizjologiczne organizmu. Celem pracy jest poznanie aktywności fizycznej młodzieży licealnej oraz niektórych jej uwarunkowań. Materiał i metoda. Badania zostały przeprowadzone wśród 174 uczniów uczęszczających do liceum ogólnokształcącego w Zamościu. Materiał badawczy uzyskano techniką ankietowania z wykorzystaniem autorskiego kwestionariusza ankiety, a następnie poddano analizie statystycznej nieparametrycznym testem χ2 Pearsona. Wyniki. Chłopcy częściej spędzają wolny czas uprawiając sport (p=0,005), częściej ćwiczą na lekcjach wychowania fizycznego (p=0,044) oraz przeznaczają większą ilość czasu na jednorazowe ćwiczenia fizyczne (p=0,000). Wśród dziewcząt wiodącym motywatorem ruchu jest zrzucenie lub utrzymanie prawidłowej masy ciała, natomiast wśród chłopców - przyjemność płynąca z aktywności ruchowej (p=0,012). Istotne znaczenie w kontekście zwiększenia aktywności fizycznej wśród uczniów zamieszkujących tereny wiejskie ma czynnik związany z dostępem do infrastruktury sportowej w okolicy zamieszkania. Natomiast wśród mieszkańców miast wiodącą rolę odgrywa dysponowanie odpowiednią ilością czasu (p=0,027). Wnioski. Dziewczęta stanowią grupę licealistów szczególnie zagrożoną niedoborem aktywności ruchowej. Programy promujące aktywny tryb życia powinny być ukierunkowane na kształcenie umiejętności czerpania przyjemności z ruchu oraz efektywnego zarządzania czasem wolnym. Niedostateczna liczba obiektów rekreacyjnych na terenach wiejskich stanowi istotny czynnik ograniczający dodatkową aktywność fizyczną adolescentów. Słowa kluczowe: aktywność fizyczna, wychowanie fizyczne, motywy, bariery, młodzież licealna. Summary Introduction and work aim. Physical activity constitutes one of key conditions for a healthy lifestyle. Unfortunately, as it results from the analyses only 30% of children and youth undertake physical activities, which type, frequency and intensity meets physiological needs of the body. An aim of the work is to analyze the physical activity of secondary-school youth and some of its conditions. Material and Method. Examinations were conducted amongst 174 pupils attending to comprehensive secondary school in Zamość. Research material was obtained with surveys technique using the author’s questionnaire form, and next subjected to statistical analysis with nonparametric Pearson’s χ2 statistical test. Results. Boys more often spend their free time practicing sport (p=0.005), more often exercise during physical lessons (p=0.044), and spend more time on one-off exercise (p=0.000). Amongst girls the leading motivator is to lose or keep correct body weight, however amongst boys – pleasure of physical activity (p=0.012). An important in the context of increasing physical activity amongst pupils living in the countryside is a factor associated with the access to sport infrastructure in the area of residence. However, amongst residents of cities an important is appropriate amount of time (p=0.027). Conclusions. Girls constitute a group of secondary-school pupils particularly threatened with deficiency of physical activity. Programs promoting an active lifestyle should be directed to educate the ability of drawing pleasure from movement and effective time management. Insufficient number of recreational objects on country areas constitutes an important factor that limits the additional physical activity of adolescents. Keywords: physical activity, physical education, motives, restrictions, secondary-school youth.